IMPLEMENTASI AUGMENTED REALITY PADA VIRTUAL TOUR DITEMPAT WISATA KOTA BATAM - Soleh; Fajrin, Alfannisa Annurullah Fajrin (LPPM Universitas Putera Batam, 2023)
Batam City is a city located in the Riau archipelago province. Batam City is known as an industrial city and has many tourist destinations, one of which is Nuvasa Bay Batam beach, Glory Melur beach and Vio vio beach. Technology that can contribute to the field of tourist destinations is Augmented Reality technology which can combine the real world and the virtual world, using a smartphone camera it will then be processed immediately so that it will display 3D objects. The development of Virtual Reality which creates conditions or a more real atmosphere such as tours, regions or locations, namely Virtual Tour, users can find out and get to know everyone around the environment without having to see the place directly. The lack of technological knowledge can be utilized by introducing Batam City tourist destinations with Augmented Reality and Virtual Tour technology. The application was developed with Unity 3D and Vuforia as the database. Blender is an application that is used as a 3D modeling. It is hoped that with the Augmented Reality application in the Virtual Tour in Batam City tourism as an introduction medium so that it can attract the attention of tourists to visit.